International Refugee Law Study Perspective State Obligations to Refugees - Alarico Gomes (Focus Journal : Law Review, 2022)
In principle, international refugee law must be in line with the development of society to understand the many problems that occur in the context of international refugees, that international refugee law is expected to function or be useful in regulating and resolving complex international refugee problems in an international scope in an appropriate and fair manner. Efforts to obtain legal protection, of course, what humans want is order and regularity between the basic values of law, namely legal certainty, legal usefulness and legal justice. Although in practice the three basic values are generally in conflict, efforts must be made for the three basic values to coincide. This also applies to international refugee law in modern times, which basically aims to create legal protection for order and regularity between the basic values of law, namely legal certainty, legal usefulness and justice within the scope of international refugees. Whereas a state's obligations to refugees, based on the provisions of Article 3 of the 1951 Convention on the Status of Refugees, state parties are obliged to apply the provisions of this convention to refugees without discrimination on race, religion or country of origin.